Neurosyphilis and ocular syphilis clinical and cerebrospinal fluid characteristics: a case series - Borges, Conrado Regis; Almeida, Sérgio Monteiro de; Sue, Karen; Koslyk, Jéssyca Luana Alves; Sato, Mario Teruo; Shiokawa, Naoye; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2018)
Background During the first decade of this century, a significant increase in the incidence of syphilis was documented.Objective To study clinical and laboratory characteristics of central nervous system and ocular syphilis.Methods A retrospective case series of 13 patients with a clinical and laboratory diagnosis of neurosyphilis and/or ocular syphilis who had been admitted to the Neurology and Neuro-ophthalmology Service of the Hospital de Clínicas, Federal University of Paraná.Results Nine patients had a diagnosis of neurosyphilis and two of them also had ocular syphilis. Four patients had a diagnosis of ocular syphilis alone. Among the patients with a diagnosis of neurosyphilis, six had symptomatic syphilitic meningitis, of whom one manifested as cranial nerve palsy alone, one as cranial nerve palsy plus ocular syphilis, two as transverse myelitis (syphilitic meningomyelitis), one as meningitis worsening the patient’s myasthenia gravis symptoms and one as meningitis plus ocular syphilis. Additionally, we diagnosed three patients with meningovascular neurosyphilis. In the univariate analysis, patients without ocular syphilis showed greater levels of total protein and white blood cells in the cerebrospinal fluid than patients with ocular syphilis.Conclusion This Brazilian case series of patients with neurosyphilis and ocular syphilis highlights the wide variability of this disease. A high degree of diagnostic suspicion is necessary when facing neurological and ocular symptoms for rapid diagnosis and appropriate management of patients.
Keywords: syphilis; neurosyphilis, ocular syphilis